Developing Information Systems : Practical guidance for IT professionals. - Ahmed, Tahir (BCS Learning & Development Limited, 2014)
Systems development is the process of creating and maintaining information systems. This practical book provides a comprehensive introduction to the topic and can also be used as a handy reference guide by those already working in the field. It is the only textbook that supports the BCS Certificate in Systems Development.